Evidence for the Effectiveness of Jungian Psychotherapy: A Review of Empirical Studies - Christian Roesler (Behavioral Sciences, 2013)
Since the 1990s several research projects and empirical studies (process and outcome) on Jungian Psychotherapy have been conducted mainly in Germany and Switzerland. Prospective, naturalistic outcome studies and retrospective studies using standardized instruments and health insurance data as well as several qualitative studies of aspects of the psychotherapeutic process will be summarized. The studies are diligently designed and the results are well applicable to the conditions of outpatient practice. All the studies show significant improvements not only on the level of symptoms and interpersonal problems, but also on the level of personality structure and in every day life conduct. These improvements remain stable after completion of therapy over a period of up to six years. Several studies show further improvements after the end of therapy, an effect which psychoanalysis has always claimed. Health insurance data show that, after Jungian therapy, patients reduce health care utilization to a level even below the average of the total population. Results of several studies show that Jungian treatment moves patients from a level of severe symptoms to a level where one can speak of psychological health. These significant changes are reached by Jungian therapy with an average of 90 sessions, which makes Jungian psychotherapy an effective and cost-effective method. Process studies support Jungian theories on psychodynamics and elements of change in the therapeutic process. So finally, Jungian psychotherapy has reached the point where it can be called an empirically proven, effective method.